Photoreceptor proteins as cancer-retina antigens - Bazhin, Alexandr V.; Schadendorf, Dirk; Umansky, Viktor; Eichmüller, Stefan B. (International journal of cancer, 2007)
Melanocytes, melanoma and photoreceptor cells are of neuroectodermal origin and have a certain sensitivity to light. In this study, we present evidence for photoreceptor proteins that are responsible for visual transduction and its regulation function as a new class of cancer antigens in melanoma. Visual rhodopsin, transducin, cGMP-phosphodiesterase 6, cGMP-dependent channels, guanylyl cyclase, rhodopsin kinase, recoverin and arrestin are expressed in melanoma and can induce antibody responses in patients. Melanocytes also express mRNA of all photoreceptor genes besides transducin, but were devoid of the corresponding protein, which was tested for rhodopsin, cGMP-phosphodiesterase, guanylyl cyclase and recoverin. Furthermore, we show for the first time that some healthy tissues express mRNA of these genes, but never protein. Expression profiles and autoantibody responses were confirmed in the MT/ret and the HGFtg/Ink4a−/− transgenic mouse melanoma models. We propose a molecular transition of cancer-retina antigens from mRNA expression in melanocytes to protein expression in melanoma. Our work provides the basis for analyzing regulation of photoreceptor gene expression in normal and malignant cells as well as possible therapeutic tumor targeting using the newly defined class of cancer-retina antigens.